Electron microscopy of Mg/TiO 2 photocatalyst morphology for deep desulfurization of diesel - Yin, Y.C. (American Institute of Physics Inc., 2015)
A series of Mg/TiO 2 photocatalysts were prepared and characterized using Field Emission Scanning Electron Microscopy (FESEM) and High-Resolution Transmission Electron Microscopy (HRTEM). The average particle sizes of the photocatalysts were ranging from 25.7 to 35.8 nm. Incorporation of Mg on TiO 2 did not lead to any surface lattice distortion to TiO 2 . HRTEM data indicated the presence of MgO and Mg(OH) 2 mixture at low Mg loading while at higher Mg loading, the presence of lamellar Mg-oxyhydroxide intermediates and Mg(OH) 2 . Â© 2015 AIP Publishing LLC.